Constant pioneers: The citation frontiers of indexing theory in the ISKO international proceedings - Guimarães, José Augusto Chaves [UNESP]; Tennis, Joseph T. (My University, 2012)
Presents a citation analysis of indexing research in the ISKO Proceedings. Understanding that there are different traditions of research into indexing, we look for evidence of this in the citing and cited authors. Three areas of cited and citing authors surface, after applying Price's elitism analysis, each roughly corresponding to geographic distributions.